ANALISIS TIME SERIES SEDERHANA PADA JUMLAH KUNJUNGAN WISATAWAN MANCANEGARA DI BATAM - Kurniawati, Ely (UP2M SEKOLAH TINGGI ILMU EKONOMI GALILEO, 2018)
Due to its geographic location near Singapore and Malaysia, Batam has potential contribution in developing tourism sector. The number of tourist arrival is one of indicator in the development of tourism sector. This variable needs to be forecasted to give input in the development of this sector. Simple time series method is used to model this conditions, they are Winters, Decomposition and naÃ¯ve methods. Those three methods are part of time series analysis suitable for seasonal and trended data. Based on analysis, found that number of tourist arrival has a seasonal and trend pattern, which suit the requirement of those three methods. From the analysis performed, and based on RMSE and MAPE, Winters methods is best in modelling the training data, Decomposition methods is best in modelling testing data.